Meanings of work for women in the tattoo profession - Silva, Richeila Gabriele Moura da; Correia-Lima, Bruno Chaves; Lima, Tereza Cristina Batista de; Araújo, Rafaela de Almeida (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: This study investigates the meanings attributed to work by female tattoo artists, a profession historically dominated by men. The female presence in this field challenges gender norms and puts pressure on the boundaries between art, work, and recognition, especially in a context of social transformations that still carry strong stigmas and prejudice. Purpose: To analyze how female tattoo artists perceive and attribute meaning to their work. The study aims to explore the individual, organizational, and social dimensions that influence these perceptions. Method: This is a qualitative study based on semi-structured interviews with 14 female tattoo artists from Fortaleza, Ceará (Brazil). Data analysis was conducted using content analysis, structured into three dimensions: individual, organizational, and social. Each dimension was detailed into categories and recording units. The software ATLAS.ti was employed for data organization and coding. Results: The findings indicate that the participants associate their work with a strong sense of autonomy, personal fulfillment, and artistic expression. They also highlight the positive impact of their practice on clients’ lives as a meaningful aspect of their professional identity. Nevertheless, they report challenges related to gender-based discrimination and persistent social stigma surrounding the profession. Although the field has gained increased recognition, cultural barriers and prejudices remain. Conclusions: The study provides theoretical contributions by expanding the understanding of work meaning in professions related to creativity and gender. Methodologically, the use of content analysis was effective in capturing the nuances of participants’ perceptions. From a social perspective, the findings underscore the persistence of prejudices associated with tattooing and gender stigma. The value of the research lies in examining an emerging and underrepresented profession, offering new insights to the field of gender and work studies.